ANALISIS KELAYAKAN FINANSIAL USAHATANI KOPI ARABIKA DI DESA BANDUNG BARU KECAMATAN KABAWETAN KABUPATEN KEPAHIANG - Wahyuni, Siska Sri; Utama, Satria Putra; Mulyasari, Gita (Jurnal AGRISEP, 2012)
The research was conducted in Desa Bandung Baru, Subdistrict Kabawetan Kepahiang Regency Bengkulu Province. The purpose of this study were : 1) To Analyze the financial feasibility of arabica coffee farm in village of Bandung Baru subdistrict Kabawetan Kepahiang regency Bengkulu Province from the financial aspect, 2) To Calculate the payback period and the level of sensitivity against the declaine in Arabica coffee farm production, price reductions, increased investment costs, operating costs and maintenance. Determination of respondent carried out using Stratified Random Sampling, data consist of primary data and secondary data. The number of respondent in this study were 40 samples. The results of this study indicate that the views of financial aspects of Arabica coffee farm worth the effort, this is apparent from the Net B/C is 2,17 (>1), Gross B/C value is 1,28 (>1), PV”/K value is 2,11 (>1), NPV of Rp. 18.847.733 and IRR value is 26,60 %. Sensitivity analysis shows that if there was increase in production 29%, price of production decreased 22% and decrease production 22%.